Perceptions among non executive staff’s towards the implementation of knowledge management in the organization. A case study of SAJ Holdings Sdn Bhd / Khair-ul-Nadhirah Mohd Khair - Mohd Khair, Khair-ul-Nadhirah (Faculty of Business and Management, 2011)
Currently, growing demand for knowledge-based products and services is changing the structure of the global economy; the role of knowledge in achieving competitive advantages is becoming an important management issue in all sectors. Knowledge management activities can assist the organization on acquiring, storing and utilizing knowledge for process such as problem solving, dynamic learning, strategic planning and decision-making (Sveiby, 1997; Takeuchi & Nonaka, 2004). In addition, knowledge management has the ability to protect intellectual assets from decay and loss (Armistead, 1999; Awad & Ghaziri, 2003; Cecez-Kecmanovic & Kay, 2002; Devaenport, De Long & Beers, 1998; Lang, 2004; Poh, 2001) While Drucker (1993) described knowledge is rather than capital or labor as the only meaningful resource in the knowledge society. Although, there is recognition that the knowledge society and the knowledge economy have arrived, and the knowledge is a key and business asset, organizations are still in the early stages of business asset, understanding the implications of knowledge management.